Cavernous transformation of the portal vein in pancreatic cancer surgery: venous bypass graft first - Schmidt, Thomas; Strobel, Oliver; Schneider, Martin; Diener, Markus K.; Berchtold, Christoph; Mihaljevic, André Leopold; Mehrabi, Arianeb; Müller, Beat P.; Hackert, Thilo; Büchler, Markus W. (Langenbeck's archives of surgery, 2020)
In recent years, several techniques have been introduced to allow safe oncologic resections of cancers of the pancreatic head. While resections of the mesenterico-portal axis became now a part of the routine treatment, patients with a cavernous transformation of the portal vein still pose a surgical challenge and are regularly deemed unresectable.